Daurisoline inhibits glycolysis of lung cancer by targeting the AKT-HK2 axis - Shi-Ming Tan; Lan Luo; Yi-Fu He; Wei Li; Xin-Xing Wan (Cancer Biology & Therapy)
Lung cancer, one of the most prevalent tumors, remains a clinical challenge with a poor five-year survival rate. Daurisoline, a bis-benzylisoquinoline alkaloid derived from the traditional Chinese herb Menispermum dauricum, is known to suppress tumor growth effectively. However, its precise mechanism of action remains unclear. In this study, we demonstrate that Daurisoline targets glycolysis and reduces the protein level of HK2, thereby inhibiting lung cancer progression. Mechanistic investigations reveal that Daurisoline directly binds to AKT and antagonizes the AKT-GSK3β-c-Myc-HK2 signaling axis. Furthermore, in an animal model, we validate the in vivo anti-tumor effect of Daurisoline without any observable side effects. Overall, our findings suggest that Daurisoline holds potential as an anti-tumor agent through its targeting of glycolysis.